EFFECT OF FLY-ASH ON THE STRENGTH DEVELOPMENT OF COASTAL SOILS-A CASE STUDY FOR THE SOUTHERN COASTAL ZONE OF BANGLADESH (Malaysian Journal of Civil Engineering, 2021)
The rapid demand for urbanization expands the requirements of infrastructures and owing to the scarcity of available firm land; people are now built structures on soft soils. However, the application of a deep foundation for a low-rise structure may not be economically feasible for developing countries. The economic, as well as safe foundation, can be ensured by adopting traditional ground stability approaches. However, replacement of the industrial by-product, which possess minimum environmental threat may be a plausible option for ground stability. Therefore, an attempt is taken in this research to study the improvement of soft coastal soil by replacing with eco-friendly fly ash. The eastern bank of the river Karnaphuli, which has increasing industrial and residential demand is taken as a case study in this research. A series of experimental set-ups have been conducted to evaluate the strength development with different fly ash contents. It is found that the strength of fly ash treated soils increases with fly ash content up to a threshold value, and beyond that, the strength decreases. In addition, compaction and plasticity characteristics are also investigated through experimental observations and show better performance criteria with increasing fly ash contents. In a nutshell, this approach of replacing fly ash is suitable for coastal soil, and the experimental investigation reveals that an optimum 20% of fly ash content is justified.